(untitled) (Simbiótica. Revista Eletrônica, 2026)
The regulatory framework for communication was central to the agenda of social movements through the “To Express Freedom” Campaign of the FNDC. The objective of this article is to analyze the relationship between the context of political opportunities/restrictions and the repertoires of action within this mobilization. Documentary research is conducted using materials produced by the movement during the Campaign, such as the magazine Mídia Com Democracia; publications on social networks; the platform for a media law; and public protest demonstrations. These sources reveal strategic decisions, Campaign actions, and their motivations, which allow, through discourse analysis, the establishment of a relationship between political context and repertoires. It is concluded that institutional and extra-institutional actions were adopted, both proactive and conflictive, in a contingent and informal relationship with the State, resulting from the political-institutional context generated by progressive governments, the ConfeCom, and the reorganization of civil society in favor of a common agenda.